2019
DOI: 10.1021/acsami.9b10954
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Ferroptotic Antitumor Efficacy via Site-Specific Amplification of Tailored Lipid Peroxidation

Abstract: Ferroptosis is an iron-dependent cell death pathway that can eradicate certain apoptosis-insensitive cancer cells. The ferroptosis-inducing molecules are tailored lipid peroxides whose efficacy is compromised in hypoxic solid tumor and lack of tumor selectivity. It has been demonstrated that ascorbate (Asc) in pharmacological concentrations can selectively kill cancer cells via accumulating hydrogen peroxide (H 2 O 2 ) only in tumor extracellular fluids. It was hypothesized that Asc-induced, selective enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 60 publications
0
68
1
Order By: Relevance
“…Recently, nanocarriers have been proposed as an efficient approach to induce ferroptosis in cancer cells in vitro and in vivo [121]. Doxorubicin, packed into mesoporous carbon nanoparticles, induces ferroptosis in breast cancer (MCF7) cells, in A549 cells, and in human cervical carcinoma (HeLa) cells [122].…”
Section: Ferroptosis Is a New Promising Target For Cancer Treatmentmentioning
confidence: 99%
“…Recently, nanocarriers have been proposed as an efficient approach to induce ferroptosis in cancer cells in vitro and in vivo [121]. Doxorubicin, packed into mesoporous carbon nanoparticles, induces ferroptosis in breast cancer (MCF7) cells, in A549 cells, and in human cervical carcinoma (HeLa) cells [122].…”
Section: Ferroptosis Is a New Promising Target For Cancer Treatmentmentioning
confidence: 99%
“…An et al combined nanocarriers loading Fe 3+ and RSL3 with ascorbate (Asc), which was reported to selectively kill cancer cells by accumulating hydrogen peroxide (H 2 O 2 ) only in tumour extracellular fluids, to induce ferroptosis in cancer cells more accurately [111].…”
Section: Development Of Ferroptotic Therapeutic Strategiesmentioning
confidence: 99%
“…DOPA has been widely employed for engineering inorganic-organic hybrid drug delivery particles. [40,41] DSPE-PEG was deposited onto CA4P or DOPA layer through hydrophobic interaction to stabilize nanocarriers via steric mechanism.…”
Section: Resultsmentioning
confidence: 99%